KEBIJAKAN FISKAL DALAM EKONOMI ISLAM - May sarah; Rahma Almira Hani; Atikah Fara (LPPM - STIE SAKTI ALAM KERINCI, 2023)
One of the government's policies, fiscal policy involves public borrowing, taxation, and spending to achieve stability of government goals, asset formation, healthy level of economic development, and balance of income and welfare. which regulates or manages state revenues in order to maintain stability and encourage economic growth. Islamic sharia-based fiscal regulations. The realization of human well-being and the resolution of all individual, group and communal problems are these goals. The results of this discussion indicate that fiscal policy in Islam is expected to be able to carry out the functions of distribution, allocation and stabilization of a country that has special characteristics in state revenues and expenditures. The research methodology used is liberarian studies. Islamic policy, which is carried out in a place called Baitul Mal, has extensive experience using various fiscal policy instruments since the time of the Prophet and the Caliphate. Islamic history documents the existence of fiscal policy from the beginning of trade to the peak of Islam during the caliphate.